2017
DOI: 10.1103/physrevb.96.085436
|View full text |Cite
|
Sign up to set email alerts
|

Electro-optical properties of phosphorene quantum dots

Abstract: We study electronic and optical properties of single layer phosphorene quantum dots with various shapes, sizes, and edge types (including disordered edges) subjected to an external electric field normal to the structure plane. Compared to graphene quantum dots, in phosphorene clusters of similar shape and size there is a set of edge states with energies dispersed at around the Fermi level. These states make the majority of phosphorene quantum dots metallic and enrich the phosphorene absorption gap with low-ene… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 89 publications
2
34
0
1
Order By: Relevance
“…Recall that the distances between two P atoms within the sublayer and in different sublayers are 2.164 Å and 2.207 Å, respectively (see Fig.3 in ref. [12]). In order to verify the stability of the selected PQDs, we calculated their binding energies by using the following equation: E B = (N H E H +N S E S +N P E P -E C )/N.…”
Section: Resultsmentioning
confidence: 99%
“…Recall that the distances between two P atoms within the sublayer and in different sublayers are 2.164 Å and 2.207 Å, respectively (see Fig.3 in ref. [12]). In order to verify the stability of the selected PQDs, we calculated their binding energies by using the following equation: E B = (N H E H +N S E S +N P E P -E C )/N.…”
Section: Resultsmentioning
confidence: 99%
“…[36] are given in Table I together with the distances between the corresponding sites of the lattice. In order to study the optical properties of phosphorene quantum dots we calculate their optical absorption cross sections [20,37,38]:…”
Section: Theoretical Modelmentioning
confidence: 99%
“…It is predicted that the edge states play a considerable role in PQDs electronic and optical properties. For example, PQDs can be conducting, semiconducting, or insulating depending on the applied electric and magnetic fields, shape and edge termination of the quantum dots [14,[19][20][21][22]. Recently it was shown that electron pair repulsion in black phosphorus (PB) is responsible for the peculiar edge effects and can be used in the damage-free surface functionalization of PB [23].…”
Section: Introductionmentioning
confidence: 99%
“…В [16] изучены электронные и оптические свойства однослойных квантовых точек фосфорена, имеющих различную форму. По сравнению с графеновыми квантовыми точками, в фосфореновых кластерах, имеющих одинаковую форму и размер, имеется набор граничных состояний с энергиями, расположенными вокруг уровня Ферми.…”
Section: Introductionunclassified